Using Small Branches of Bombax ceiba Instead of Stem Bark for a Conservative Sourcing Approach: Comparative Studies of Chemical Profiling by LC‐MS, GC‐MS, and HPLC. Issue 5 (1st February 2023) - Kumar Meena, Ajay; Ilavarasan, Raju; Ojha, Vikas; Perumal, Ayyam; Singh, Ravindra; Srikanth, Narayanam; Singh Dhiman, Kartar
Abstract: The purpose of the current study piece is to use short branches rather than stem bark to take a conservative approach to the Bombax ceiba plant. Similarities were found in the HPLC, LCMS, and GCMS data of the plant's stem bark and tiny branches. Analysis using liquid chromatography‐mass spectrometry (LC‐MS) of abundant medicinal phytochemicals of Bombax ceiba and its Molecular Docking Interaction with AKT Protein Kinase, Human Acetyl Choline Esterase, and Pancreatic Lipase Colipase Target Protein. According to the HPLC study results, Bombax ceiba stem bark contains 0.359 % lupeol, whereas tiny branches have 0.039 %. Three compounds have good binding energy (Kcal/mol) with Human acetyl choline esterase, while seven compounds have very good binding energy (Kcal/mol) with AKT Protein kinase and Pancreatic Lipase Colipase. Small branches are essentially identical to stem bark in terms of their chemical composition that makes them active against certain target proteins. Abstract : We worked on conservative approach of B. ceiba plant and performed Molecular Docking study of biomarker against AKT Protein kinase, Human acetyl choline esterase and pancreatic lipase colipase target protein. The small branches have almost similar activity like stem bark against particular target proteins. In view of this study, the stem bark of the plant can be replaced with small branches.